Controls on porosity preservation within a Jurassic oolitic reservoir complex, UAE. (December 2017) - Hollis, Cathy; Lawrence, David A.; Deville de Perière, Matthieu; Al Darmaki, Fatima
Abstract: The Upper Jurassic Arab Formation, onshore southern UAE, comprises an upward-shallowing succession of slope to basinal wackestones (lower Arab D Member) oolitic grainstone (upper Arab D Member) and peritidal - subtidal carbonate-evaporites (Arab A-C Members). This study focuses on the upper Arab D Member, the volumetrically most important reservoir unit in the field, which is dominated by oolitic and skeletal oolitic grainstones with high porosity and moderate to low permeability. Through much of the upper Arab D Member, porosity has been inverted so that ooids are porous and interparticle macropores cemented by pre-compactional non-ferroan calcite. Cementation is most pervasive within cross-bedded skeletal oolitic grainstones, occluding primary interparticle macropores and biomoulds and penetrating the margins of altered ooids. In contrast, bioturbated pack-grainstones are often only partially cemented, and retain a well-connected primary interparticle macropore network. Ooid alteration and porosity inversion in oolitic grainstones is often explained by open-system recrystallization by meteoric fluids during platform emergence. In this study, however, deposition took place in an arid basin that was eventually desiccated and hence the supply of groundwater would have been limited. The high concentrations of Mg and Sr within both the bulk rock limestone and cements suggest recrystallization could have occurred by marine pore fluids whilst, petrographical and geochemical homogeneity, including a narrow range of δ 18 Ocalcite (−5%0 ± 1%0), can be explained by closed-system stabilization of aragonite. Subsequent calcite cemented fractures and drusy, sparry pore filling calcite contain petroleum and aqueous inclusions with homogenisation temperatures up to 150 °C The preservation of the highest macropore volumes on the palaeocrest of the field, and an off-flank reduction in porosity and permeability, suggests that oil emplacement terminated calcite cementation. The results of this study demonstrate that a major reorganization of porosity can occur during the stablisation of metastable grains without invoking open-system circulation of meteoric water. Overall, the data provides an insight into possible controls on so-called porosity inversion, a poorly understood phenomenon in many hydrocarbon-bearing oolitic grainstone reservoirs. Highlights: This paper focuses on porosity evolution in the Arab D (Upper) reservoir in an onshore gas field, UAE. The reservoir has undergone porosity inversion which is a poorly understood process in many carbonate reservoirs. We hypothesise a closed-system redistribution of porosity by stabilization of metastable aragonitic ooids during early burial. Oil emplacement terminated diagenesis and preserved pores on the field crest. Such a model could be applied to other age-equivalent, Jurassic reservoirs.